Enzymatic pretreatment for the enhancement of beetroot drying process - Graciola, Keli Cristina; Costa, Bruna Roos; Sant’Anna, Voltaire; Klein, Manuela Poletto; de Moraes, Kelly (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate the use of cellulase and pectinase as pretreatments for the drying of beetroot (Beta vulgaris). The experiment consisted of slices of beetroots subjected to four different treatments before the drying procedure, as follows: no wet pretreatment; wet pretreatment without enzymes; pectinase solution pretreatment; and cellulase solution pretreatment. Treatments were compared for drying rates, color change, content of betalains, and plant tissue structure. A modified Page model was used to describe the drying process. The enzymatic pretreatments did not improve the drying kinetics, although they changed the plant tissue structure. A negative influence on the drying was observed when pectinase was used; however, no effect was observed when cellulase was used. Slices treated with cellulase remained unchanged for color. Slices treated with pectinase showed significant changes of color, in comparison with the control treatments. The enzymatic pretreatments studied did not change the betalain concentrations and showed similar drying performance in the comparison with control treatments. Cellulase pretreatment is promising because it does not change the beetroot color or the betalain concentration.